Neighborhood scheme selection for classification with SCRD method - Stabingis, Giedrius; Stabingienė, Lijana (Lietuvos matematikos rinkinys, 2015)
When using Spatial Correlation Rule with Distance (SCRD) the selection of the neighborhood scheme influences classification accuracy. Spatial dependency in different situations remains at various distances, so, according to this, in applications it is important to choose a suitable neighborhood scheme. In the earlier papers of the authors, the nearest neighbor scheme was used. In this paper, several different neighborhood schemes are examined by large experiment.
Keywords: spatial classification; supervised classification; neighborhood; neighborhood schemes